2016
DOI: 10.1684/ejd.2015.2706
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and associated factors of seborrheic dermatitis in Korea

Abstract: Background: Systematic investigations of clinical manifestation and factors associated with the severity of seborrheic dermatitis (SD) have rarely been reported in Asia. Objectives: We investigated the clinical manifestation and associated factors of SD. Materials & Methods: Patients were asked to fill a self-questionnaire including symptom severity and aggravating factors. We evaluated objective severity and involved sites of SD. Patients were categorized into three groups; young age group (age <30), middle a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 12 publications
3
10
0
Order By: Relevance
“…Another population‐based study using data from the Rotterdam Study indicated that SD is more prevalent in men, as well as in middle‐aged and elderly people, especially during winter 21 . Two other studies conducted in Korea and Turkey also reported a male‐ and elderly predominant pattern in patients with SD compared with controls 22,23 . We found that SD was more prevalent in men and in elderly participants, which corroborated with previous study findings.…”
Section: Discussionsupporting
confidence: 90%
“…Another population‐based study using data from the Rotterdam Study indicated that SD is more prevalent in men, as well as in middle‐aged and elderly people, especially during winter 21 . Two other studies conducted in Korea and Turkey also reported a male‐ and elderly predominant pattern in patients with SD compared with controls 22,23 . We found that SD was more prevalent in men and in elderly participants, which corroborated with previous study findings.…”
Section: Discussionsupporting
confidence: 90%
“…The skin-related comorbidity and the triggering factors determined, support the experience from clinical care and from the few studies published, 3 , 18 , 19 suggesting that acne, seborrheic eczema, folliculitis and rosacea are associated with seborrhea.…”
Section: Discussionsupporting
confidence: 63%
“…Some high‐quality prevalence studies focus on specific age groups such as the Rotterdam Study on an elderly population . Others focus on the systemic comorbidity of seborrhoeic dermatitis . By contrast, data on its association with other skin conditions are scarce.…”
mentioning
confidence: 99%